The Central Teachers Institute and the Steps of Establishing the Teachers College at Al-Mustansiriyah University in the Year 1993 to the Year 2003: A Historical Study (Journal of the College of Basic Education, 2025)
The Central Teachers Institute in Baghdad is one of the educational institutions that suffers from the process of preparing teachers in Iraq. It was established in Baghdad in the Adhamiya area and then moved to a new building located in the Sabaa Abkar area - Al-Rabi'a neighborhood. It continued to graduate a number of teachers to provide primary schools with new educational capacities, until the new educational policy in Iraq emerged from the social and political philosophy of the educational policy trends during the academic year 1992-1993 by establishing colleges specialized in preparing teachers in all Iraqi governorates, in order to graduate university teachers and put them in primary and secondary schools after qualifying them educationally, scientifically and culturally with curricula that differ from what was in the Teachers Institute, which depended on studying specialized subjects since the first year of accepting student teachers in the departments they wanted, while the process of preparing teachers moved after the establishment of the Teachers College at Al-Mustansiriya University on the ruins of the Central Teachers Institute to be concerned with graduating university teachers who studied general subjects in their first years and then moving in the second stage to specialization in the branches present in the college and continuing to study secondary subjects in addition to the basic specialized subjects, and it continued in this way Despite the developments that have occurred in the College of Teachers since its establishment in 1993 until 2003 and its transformation into the College of Basic Education.